Transcription Factor Networks in B-Lymphocyte Lineage Commitment - Gustafsson, Johanna Tingvall ; 0000-0002-7359-6584; Hellerstedt, Kim; Sigvardsson, Mikael (Encyclopedia of Immunobiology, 2025)
The process that generates the different types of highly differentiated cells in the immune system from hematopoietic stem cells involves not only the acquisition of lineage-specific features, but also the permanent repression of alternative developmental programs and the preservation of lineage identity. The well-charted developmental trajectory of early B-cell development, in combination with abundant loss and gain of function mouse models, provides detailed insights into the molecular mechanisms of B-lymphocyte commitment. This process entails the interplay of transcription factors such as IKZF1, TCF3, EBF1 and PAX5, creating gene regulatory networks that serve to activate lineage-restricted genes and suppress the expression of genes associated with alternative cell fates. The functions of these transcription factors are influenced by the epigenetic landscape, as well as external signals, creating an integrated network that balances and drives cellular differentiation. The same regulatory networks are commonly targeted by mutations in B-lymphoid malignancies, thereby linking development to disease. This chapter describes the developmental trajectory of B-cell development and the key regulators of normal and malignant differentiation and lineage commitment in the bone marrow.
Keywords: Acute lymphoblastic leukemia; B-lymphocyte; Bone marrow; Development; Enhancer elements; Epigenetics; Gene regulatory networks; Lineage commitment; Transcription factors